Association of ACE gene polymorphisms with cardiovascular events in patients after elective percutaneous coronary interventions - E. O. Nalesnik; E. F. Muslimova; S. A. Afanasiev; A. N. Repin (Российский кардиологический журнал, 2022)
Aim. To reveal the association of the INS/DEL polymorphism of the angiotensinconverting enzyme (ACE) gene with acute and long-term complications of elective percutaneous coronary interventions (PCI).Material and methods. This prospective study included 286 patients with chronic coronary artery disease who underwent elective endovascular myocardial revascularization in accordance with current guidelines. The ACE gene INS/DEL (I/D) polymorphism was determined in patients using polymerase chain reaction. Acute periprocedural complications were recorded. Acute myocardial injury (AMI) was detected in 30,4% of patients. Type 4a acute myocardial infarction developed in 3,1% of patients. A significant decrease in the glomerular filtration rate by more than 30% due to periprocedural acute kidney injury (AKI) was diagnosed in 6,5% of patients. Outcomes of elective PCIs were assessed after 4 years via telephone interviews. Cardiovascular and any-cause mortality was 3,6% and 5,1%, respectively. Acute coronary syndrome during the follow-up period developed in 15,2%, while cerebrovascular accident — in 5,4% of patients. Any-stent thrombosis was detected in 10%, and restenosis ≥30% — in 21,8% of patients. Statistical analysis was carried out using the STATISTICA 10. The odds ratio (OR) was calculated with a 95% confidence interval.Results. Analysis of the association of ACE gene I/D polymorphism with acute and long-term complications of the PCI revealed that the presence of I allele is associated with the risk of periprocedural AKI (p=0,017; OR, 2,627 (1,161- 5,947)), as well as long-term cardiovascular events, vascular complications such as acute coronary syndrome (p=0,045; OR, 1,610 (1,007-2,573)) and stent thrombosis (p=0,01; OR, 2,073 (1,178-3,650)). The presence of genotype II further increases the risk of AKI (p=0,029; OR, 5,138 (1,022-25,824)), any acute clinical complications of PCI (p=0,041; OR, 1,996 (1,024-3,980)), and stent thrombosis (p=0,018, OR, 3,498 (1,178-10,392)).Conclusion. In patients with chronic coronary artery disease, the carriage of allele I and genotype II of the ACE gene I/D polymorphism is associated with the risk of acute clinical complications of elective PCI, periprocedural AKI, as well as the risk of stent thrombosis and acute coronary syndrome within 4-year follow-up period after PCI.